Incorporating Pronunciation in Day-to-Day Activities - Dam Mai Ly, Linh (Issues in Language Instruction, 2018)
Teaching pronunciation by itself is hard to do without context; it should be related to specific lessons. Moreover, pronunciation is a necessary component for students in everyday and academic tasks. This presentation offers warm-up activities that EFL instructors can use on a daily basis to help students develop pronunciation skills.